CORRELATION BETWEEN ORGANIZATIONAL FACTORS AND PERSONAL CHARACTERISTICS WITH OCCUPATIONAL STRESS AMONG ADMINISTRATION EMPLOYEES OF X HOSPITAL - Natasya Ezra Hotnida; Azizah Musliha Fitri; Chahya Kharin Herbawani (Journal of Public Health Research and Community Health Development, 2021)
Occupational stress occurs to anyone, including hospital workers who are at high risk of depression, commit suicide, and experience excessive anxiety. The stress was one of the long-standing problems that occur among them. This study aimed to determine the risk of occupational stress among administration employees at X Hospital. This research used a quantitative with cross-sectional approach. The sample for this research was all 58 of the office employees in X Hospital. The method used in this research was the total sampling method. This research was undertaken from March to June 2020. The research instrument was a questionnaire that includes personal characteristics (age, sex, and working period), occupational stress, and organizational factors (mental workload, working hours, and income). The result showed that 77.6% of employees deal with heavy occupational stress. The statistical analysis result showed that working mental workload (p-value= 0.009) had a significant correlation with occupational stress. Meanwhile, age (p-value = 0.404), sex (p-value = 0.094), working period (p-value = 0.480), working hours (p-value = 0.073), and income (p-value = 0.862) did not have significant correlation with occupational stress. Therefore, the hospital should pay more attention to employees, their mental health, and their occupational stress.Keywords: mental workload, income, age